Dining with the Police<subtitle>Resistance and Acceptance of Community Policing</subtitle> - Mads Madsen; Tobias Kammersgaard (Nordic Journal of Studies in Policing)
While community policing has been widely studied with regard to policing practices and attitudes of personnel engaged in community work, the reception of community policing from a community perspective has received considerably less attention. Based on 10 months of fieldwork in a Danish neighbourhood officially designated as a ghetto, this article explores local residentsʼ reception of a specific community policing initiative. We find that community policing initiatives, while possibly benevolent in intent, might not always be received enthusiastically by all segments of the community. We argue that acceptance or rejection of such initiatives depends on the ability of the police to inscribe its initiatives into the social processes which constitute the social dynamics of the community and that a reflexive awareness of social relations between the police and the community can help the police reach distrusting community groups.